IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL USING PHET SIMULATION ON MOMENTUM AND IMPULS TO IMPROVE STUDENT LEARNING OUTCOMES OF SMK INFORMATIKA AL QOLAM LABANG - RIKA NUR RAMADHANIYAH, DWI; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2018)
This research aims to analyze student?s leaning outcomes after applied guided inquiry learning model using PhET Simulation. Type of this research is pre-experimental with one group pretest-posttest design, and it uses one class as experiment and one class as replication. Samples are students of class XI-1 and XI-2 Woman in SMK Informatika Al Qolam Labang, which had been tested normality and homogeneity tests, all two classes are distributed normally and homogeneous. Variables of this research include independent variable is giving a treatment guided inquiry learning model, dependent variable is student learning outcomes, implementation of learning, and students? response, while control variable is teacher, allocation time, momentum and impuls. It is known that proposed hypothesis, H0 is non significant gain, and H1 is significant gain. Based on t-test analysis, it is found that tcalculation ? ttabel., therefore H0 is rejected and H1 is accepted with a 5 % error level. This result shows student learning outcomes in all two classes are XI-1 and XI-2 Woman have increased significantly with n-gain score 0,68 and 0,67. Skill?s average and attitudes? average score in all two classes belong good category.